Excimer Laser Correction of Myopia in Patients with Visually Intense Work — Is It Necessary to Determine the Form of Accommodative Asthenopia? - E. I. Belikova; D. V. Gatilov; I. G. Ovechkin; E. N. Eskina (Oftalʹmologiâ)
Рurpose — to study the frequency of occurrence of various forms of accommodative asthenopia (AA) in patients with visually stressful work (VSW) with different degrees of myopia planning LASIK.Methods. As part of the preoperative examination, 300 patients with VSW were under observation. There were three groups of equal age and gender, corresponding to weak (up to 3.0 diopters, 100 patients), moderate (3.25–6.0 diopters, 100 patients ) and high (6.25–8.0 diopters, 100 patients) degrees of myopia. All patients underwent objective accommodation using the Righton Speedy-I device (Japan) with further calculation of the coefficient of microfluctuations of the ciliary muscle of the eye (KMF). Diagnosis of the type of AA was carried out according to the following indicators: with KMF less than 53.0 rel. un. — asthenic form of accommodative asthenopia (AFAA), pathology; at KMF from 53.0 to 58.0 rel. — norm; at KMF more than 58.0 rel.un. — Habitual Excessive Tension of Accommodation (HETA), pathology.Results. The incidence of AA (any form) was 51–57 % and weakly depended on the degree of myopia. A significant increase (compared with the literature data) in patients with AA according to the results of this work is due to the following factors: the examination of patients exclusively with VSW, who daily perform professional visual activity at the time of the examination, as well as a wide (24–34 years) the age range of the subjects. The probability of occurrence of HETA and AFAA is quite comparable and amounted to 29–36 % and 21–23 %, respectively. The obtained results are illustrated by typical accomodograms. Conclusion: the high incidence of both forms of AA actualizes further research aimed at assessing the dynamics of the state of the accommodative system of the eye after excimer laser surgery for myopia, as well as the development of a method for correcting AA, taking into account a personalized approach that allows performing the correct diagnosis of various forms of AA (HETA, AFAA), which, ultimately, will provide adequate treatment from the position of choosing both the actual method (physical factor) and the required optical, amplitude and time parameters of exposure.